Hybrid classification: the case of the acquisition procedure documentation within and ouside the Public Contracts information systems in Alto Adige Region - Francesca Delneri (JLIS.it, 2017)
With reference to the acquisition procedures, the related documentation is created and managed mostly on the platform of the subcontracting institution, partly on the Alto Adige Public Sector Contracts information system. With a partial integration between this system and the platform made available by the Agenzia per i procedimenti e la vigilanza in materia di contratti pubblici di lavori, servizi e forniture, classification and filing information can be assigned to the documents coming from both platform, while the reunification of documents related to the same process is transferred to the preservation system as unique archive of the administration.